1967
DOI: 10.1172/jci105598
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Intracellular pH of Skeletal Muscle with pH-sensitive Glass Microelectrodes*

Abstract: Summary. We used three methods to examine the relationship among intracellular pH, transmembrane potential, and extracellular pH. Singlebarreled electrodes permitted the determination of resting potential and intracellular pH with a minimum of cellular injury. Double-barreled electrodes, which incorporated a reference as well as a pH-sensitive electrode in a single tip, facilitated the direct measurement of intracellular pH without the interposition of the transmembrane potential. Triple-barreled electrodes pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

1968
1968
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(52 citation statements)
references
References 18 publications
(17 reference statements)
3
49
0
Order By: Relevance
“…Waddell and Bates [36] in their review on intracellular pH reported a value of 6.61 -7.06 for human skeletal muscle and 6.84-7.09 for dog skeletal muscle. Carter et al [37] using glass microelectrodes, found a value of 6.0 for the intracellular pH of skeletal muscle. More recently, Roos [38] reported the intracellular pH of rat muscle to be 6.…”
Section: Resultsmentioning
confidence: 99%
“…Waddell and Bates [36] in their review on intracellular pH reported a value of 6.61 -7.06 for human skeletal muscle and 6.84-7.09 for dog skeletal muscle. Carter et al [37] using glass microelectrodes, found a value of 6.0 for the intracellular pH of skeletal muscle. More recently, Roos [38] reported the intracellular pH of rat muscle to be 6.…”
Section: Resultsmentioning
confidence: 99%
“…Intracellular electrodes, indicators, and the dissociation of weak bases and acids (39)(40)(41) have all been used to measure intracellular pH. In this study the lung pH was measured by the third technique using the bicarbonate and carbonic acid system.…”
Section: Discussionmentioning
confidence: 99%
“…Control animals received similar amounts of electrolyte-deficient diet to which had been added 1 meq of potassium chloride and 2 meq of sodium choride. At the end of 10 days, both groups of rats were anesthetized with sodium pentobarbital and muscle Em was measured by methods described previously (11). After the measurement of muscle Em, aortic blood was taken for measurement of serum electrolyte concentration, and a generous portion of anterior thigh muscle was sampled for analysis of water, sodium, potassium, and chloride.…”
Section: Methodsmentioning
confidence: 99%